TO INVESTIGATE CELL VIABILITY, CYTOTOXICITY AND ANTI-CANCEROUS PROPERTIES OF PHYLLANTHUS EMBLICA EXTRACT ON HUH-7 AND L929 CELL LINES - Rana, Sanghvi; Sharma, Mridul; Rai, Seemha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Phyllanthus emblica commonly known as Indian gooseberry or amla, has been widely recognized for its medicinal properties, including its potential anticancer effects. This study investigates its impact on Huh-7 liver cancer cells and L929 normal fibroblast cells by evaluating cell viability, cytotoxicity and oxidative stress. The MTT assay was used to assess cell viability, revealing a dose-dependent decrease in cancer cell survival while sparing normal cells. Reactive oxygen species (ROS) analysis indicated increased oxidative stress in Huh-7 cells, suggesting a role in apoptosis induction. These findings suggest that P. emblica selectively targets cancer cells while causing minimal harm to normal cells, making it a promising candidate for natural anticancer therapies. However, further studies are needed to explore its molecular mechanisms and in vivo efficacy.